STUDI POPULASI IKAN KALOSO (Scleropages jardinii) DI RAWA POMO KECAMATAN CITAK MITAK, KABUPATEN MERAUKE, PAPUA - Tjakrawidjaja, Agus H; Haryono, Haryono (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Study on the population of bony tongue/kaloso fish (Scleropages jardinii) of Papua was conducted in April 1998, located in Rawa Pomo, Kecamatan (District) of Citak Mitak, Kabupaten (Regency) Merauke, Papua.The aims were to know density,fecundity, 2 population growth and related aspects.The method used was catch per unit efforts, in 3 stations, within the area of 50.000 m width; sampling was done in each 30 minutes and fecundity was counted by eye (visual).The results showed that abundance index was 1.862 2 2ind./m ,population density 0.0043/m ,population growth 0.017 ind/m each year and fecundity range was 87-161 eggs. The most th abundance in 8 size ranged from 45.81 to 48.54 mm SL;first maturation attained at + 30 cm. We noted the fishes biodiversity in the location i.e. 21 species belongs to 18 genera and 17 families.